Analysis Of The Use Of Quick Response Code Indonesian Standard (QRIS) In Increasing Sales Transactions At Umart UMKM In Rappang Village - Febriyana, Febriyana; Muhammad Rais Rahmat Razak; Wahyudi Sofyan (SEAN Institute, 2024)
QRIS (Quick Response Code Indonesian Standard) is Bank Indonesia's new breakthrough in supporting people's digital lifestyle, especially in the field of commerce/buying and selling. UMart is a local mini market that has used QRIS as an alternative solution for payment transactions to increase sales transaction volume. In terms of use, conventional payment transactions are still very dominant compared to payment transactions via QRIS. The aim of this research is to analyze how the use of QRIS at UMART increases sales transactions. This research uses qualitative methods with the research object being UMART owners and customers who make transactions via QRIS. The data collection technique is purposive sampling through observation, interviews and documentation. This research was conducted at one of the UMKM in Rappang Village, namely UMART. The research results show that using QRIS at UMart can increase sales transactions by 8% because QRIS is very flexible, making the payment transaction process easier. The author suggests the need for outreach from both the government and merchants to the public so that people are interested in using QRIS educated in supporting Indonesia's digital economy in the future.